THE ROLE OF VITAMINS IN IRON DEFICIENCY IN PREGNANT WOMEN - Fatima Kudratovna Askarova (Scholar Express Journals, 2021)
The article deals with the problem of iron deficiency anemia as a polyetiological disease from the point of view of polydeficiency microelementosis of the pregnant woman's body. Deficiency of vitamins and minerals during pregnancy significantly increases the risk of perinatal pathology, increases infant mortality, is one of the causes of prematurity, congenital anomalies of development, affects the physical and mental development of the child. Diagnosis of polyhypovitaminosis is difficult due to the absence of  pathognomonic clinical picture.
Keywords: Iron Deficiency; Pregnancy; Iron Preparations; Vitamin-Mineral Correction